(3x-4)cube-(x+1)cube divided by (3x-4)cube+(x+1)cube=61÷189
Answers
Answered by
27
Heya User
∆ Love ya ! Thanks for the Question !!
Solution :
![\frac{ {(3x - 4)}^{3} - {(x + 1)}^{3} }{(3x - 4)^{3} + {(x + 1)}^{3} } = \frac{61}{189} \frac{ {(3x - 4)}^{3} - {(x + 1)}^{3} }{(3x - 4)^{3} + {(x + 1)}^{3} } = \frac{61}{189}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7B%283x+-+4%29%7D%5E%7B3%7D+-++%7B%28x+%2B+1%29%7D%5E%7B3%7D++%7D%7B%283x+-+4%29%5E%7B3%7D+%2B++%7B%28x+%2B+1%29%7D%5E%7B3%7D++%7D+%3D++%5Cfrac%7B61%7D%7B189%7D+)
Inverting and applying Componendo Dividendo :
![( \frac{3x - 4}{x + 1} )^{3} = \frac{250}{128} = \frac{125}{64} ( \frac{3x - 4}{x + 1} )^{3} = \frac{250}{128} = \frac{125}{64}](https://tex.z-dn.net/?f=%28+%5Cfrac%7B3x+-+4%7D%7Bx+%2B+1%7D+%29%5E%7B3%7D++%3D++%5Cfrac%7B250%7D%7B128%7D++%3D++%5Cfrac%7B125%7D%7B64%7D+)
Taking the Cube Root of Both Sides :
![\frac{3x - 4}{x + 1} = \frac{5}{4} \frac{3x - 4}{x + 1} = \frac{5}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x+-+4%7D%7Bx+%2B+1%7D++%3D++%5Cfrac%7B5%7D%7B4%7D+)
Solving the Linear Equation :
![4(3x - 4) = 5(x + 1) 4(3x - 4) = 5(x + 1)](https://tex.z-dn.net/?f=4%283x+-+4%29+%3D+5%28x+%2B+1%29)
![= > 12x - 16 = 5x + 5 = > 12x - 16 = 5x + 5](https://tex.z-dn.net/?f=++%3D++%26gt%3B+12x+-+16+%3D+5x+%2B+5)
![= > 7x = 21 = > 7x = 21](https://tex.z-dn.net/?f=+%3D++%26gt%3B+7x+%3D+21)
![= > x = 3 = > x = 3](https://tex.z-dn.net/?f=+%3D++%26gt%3B+x+%3D+3)
Hence, x = 3 is the solution ^_^
∆ Love ya ! Thanks for the Question !!
Solution :
Inverting and applying Componendo Dividendo :
Taking the Cube Root of Both Sides :
Solving the Linear Equation :
Hence, x = 3 is the solution ^_^
Answered by
0
Answer: not able to do
Step-by-step explanation:
Similar questions